The Oxford SWIFT spectrograph: First commissioning and on-sky results - Thatte, N; Tecza, M; Clarke, F; Goodsall, T; Fogarty, L; Houghton, R; Salter, G; Scott, N; Davies, R; Bouchez, A; Dekany, R (2010)
The Oxford SWIFT spectrograph, an I and z band (6500-10500 A) integral field spectrograph, is designed to operate as a facility instrument at the 200 inch Hale Telescope on Palomar Mountain, in conjunction with the Palomar laser guide star adaptive optics system PALAO (and its upgrade to PALM3000). SWIFT provides spectra at R(≡λ/Δλ)∼4000 of a contiguous two-dimensional field, 44 x 89 spatial pixels (spaxels) in size, at spatial scales of 0.235″;, 0.16″, and 0.08″ per spaxel. It employs two 250μm thick, fully depleted, extremely red sensitive 4k X 2k CCD detector arrays (manufactured by LBNL) that provide excellent quantum efficiency out to 1000 nm. We describe the commissioning observations and present the measured values of a number of instrument parameters. We also present some first science results that give a taste of the range of science programs where SWIFT can have a substantial impact. © 2010 Copyright SPIE - The International Society for Optical Engineering.